Correlation between Conformity and Verbal Abuse Tendency Behavior Through Self-Esteem: Hubungan Antara Konformitas Dengan Kecenderungan Perilaku Perundungan Verbal Melalui Harga Diri - Irwanto, Moch Surya Hakim (Psikologia : Jurnal Psikologi, 2019)
This study is based on the prevalence of verbal bullying detection among students in schools. This research takes the subject of research in SMP X with the number of 60 students. Partially there is no correlation between peer conformity with verbal bullying with significance value 0,964 (P> 0,05). There is a very significant relationship inversely between self-esteem and verbal bullying, the higher the self esteem the lower the verbal bullying. There is a conformity relationship with self-esteem with significance 0.004 (P <0.05). There is a relationship with peers with verbal bullying through the relationship between variables with direct relationship -0.03492> 0.006. This study shows the high number of peers present at the very high school level, the number of people is very high. Given from these results are benefits that can relate to verbal bullying.